Integration of intellectual property rights into Regional Trade Agreements Critical Analysis of EAC Common Market Protocol - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2015.